2005
DOI: 10.1200/jco.2005.03.7465
|View full text |Cite
|
Sign up to set email alerts
|

Should Elderly Non–Small-Cell Lung Cancer Patients Be Offered Elderly-Specific Trials? Results of a Pooled Analysis From the North Central Cancer Treatment Group

Abstract: Elderly patients in NSCLC elderly-specific trials suffered lower rates of severe adverse events with no statistically significant differences in survival. It seems that elderly-specific trials are providing quality care and helping to define optimal cancer therapy in the elderly, particularly among the "oldest of the old."

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
66
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(69 citation statements)
references
References 13 publications
2
66
0
1
Order By: Relevance
“…However, the SPIRITS trial only involved patients of less than 75 years, and extrapolation of the results from retrospective reviews or meta-analyses to the elderly patients must be done with caution because of the following limitations: (1) a small, approximately 1-month, survival advantage observed in the meta-analysis was achieved at the expense of increased toxicity (Wagner et al, 2006); (2) chemotherapy-related toxicities, such as neutropenia, anaemia, stomatitis and diarrhoea, occurred more frequently in the elderly (Trumper et al, 2006); (3) the early drop out rate was significantly higher and 5-FU dose intensity was significantly lower in the elderly when treated with combination chemotherapy containing 5-FU and cisplatin (Trumper et al, 2006); and (4) QOL, which could be impaired as the intensity of chemotherapy increases, has not been studied sufficiently. Ideally, standard treatment of AGC in elderly patients should not be based solely on retrospective subset analyses of prospective trials, and elderly specific trials are needed to define the optimal treatment for these patients (Perrone et al, 2002;Jatoi et al, 2005). Considering the ORR, OS and safety results, our study provides evidence that elderly patients with AGC could benefit from capecitabine or S-1 monotherapy with minimal adverse events.…”
Section: Discussionmentioning
confidence: 76%
“…However, the SPIRITS trial only involved patients of less than 75 years, and extrapolation of the results from retrospective reviews or meta-analyses to the elderly patients must be done with caution because of the following limitations: (1) a small, approximately 1-month, survival advantage observed in the meta-analysis was achieved at the expense of increased toxicity (Wagner et al, 2006); (2) chemotherapy-related toxicities, such as neutropenia, anaemia, stomatitis and diarrhoea, occurred more frequently in the elderly (Trumper et al, 2006); (3) the early drop out rate was significantly higher and 5-FU dose intensity was significantly lower in the elderly when treated with combination chemotherapy containing 5-FU and cisplatin (Trumper et al, 2006); and (4) QOL, which could be impaired as the intensity of chemotherapy increases, has not been studied sufficiently. Ideally, standard treatment of AGC in elderly patients should not be based solely on retrospective subset analyses of prospective trials, and elderly specific trials are needed to define the optimal treatment for these patients (Perrone et al, 2002;Jatoi et al, 2005). Considering the ORR, OS and safety results, our study provides evidence that elderly patients with AGC could benefit from capecitabine or S-1 monotherapy with minimal adverse events.…”
Section: Discussionmentioning
confidence: 76%
“…Hence, recruitment efforts must proceed hand-in-hand with initiatives to design practical trials that are readily translated to underrepresented populations. 33 Finally, healthcare providers play a vital role in the successful recruitment of underrepresented patients to cancer clinical trials. Overcoming the barriers that prevent them from recommending clinical trials to their patients is both difficult and complex.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, toxicity profile opposite age groups was usually consistent in the literature. Some clinical trials indicated that hematologic toxicity of grade 3 to 4 was higher in elderly patients (Rocha et al, 2002;Schild et al, 2003;Sequist et al, 2003;Jatoi et al, 2005), while the other trials were not (Hensing et al, 2003;Langer et al, 2003;Ansari et al, 2011). Ageing is associated with decreasesing in bone marrow reserve and myelotoxicity may be fairly increased (Deppermann et al, 2001).…”
Section: Efficacymentioning
confidence: 99%